Institutional Framework and Practice of Russian Science Diplomacy - R. O. Reinhardt; V. A. Mozebakh (Vestnik MGIMO-Universiteta)
The research deals with a relatively recent phenomenon of science diplomacy as a tool of Russian foreign policy. One of the science diplomacy tracks is 'diplomacy for science. The article investigates this track’s macroand micro-level practices to assess the overall effectiveness of Russian science diplomacy. The authors conducted an indepth analysis of primary sources and semi-structured interviews with academics and diplomats. They conclude that at the micro-level, 'diplomacy for science' is hindered by a lack of legal information on travel rules, poor consolidation of the ‘research diaspora,' and the absence of a regulatory framework to identify those eligible for consular and diplomatic support. A distrust in communication between scholars and diplomats further aggravates the uneven support for scientists across Russian diplomatic missions. At the macro-level, the institutional framework of scientific cooperation between Russia and other states appears vague, featuring non-binding memoranda of understanding and very few detailed agreements.